Critical success factors in managing sustainable indigenous businesses in Australia. Issue 1 (5th February 2018) - Bodle, Kerry; Brimble, Mark; Weaven, Scott; Frazer, Lorelle; Blue, Levon
Abstract : Purpose: The purpose of this paper is to investigate success factors pertinent to the management of Indigenous businesses through the identification of points of intervention at the systemic and structural levels. Through this approach, the economic and social values that First Nations communities attach to intangible Indigenous cultural heritage (ICH) and Indigenous cultural intellectual property (ICIP) may be both recognised and realised as assets. Design/methodology/approach: This paper adopts a multidisciplinary approach to address a global issue of economic and social significance to First Nation peoples, their businesses and the Australian Aboriginal communities. The authors adopt a First Nation epistemological standpoint that incorporates theoretical perspectives drawn from a diverse range of fields and theories (Preston, 2013 ), as well as advocate the use of Indigenist methodology for research with First Nation peoples as it is underpinned by critical race theory. Findings: The authors argue conceptually that accounting, accountability and auditing consideration are required to fully identify what is impacting the successful management of Indigenous enterprises. Specifically, in relation to accounting, Elders should be included to assist in valuing the intangible ICH and ICIP assets. Furthermore, the authors emphasise the need to improve the financial and commercial literacy levels of Indigenous entrepreneurs. Practical implications: The authors prescribe the use of tools for the accounting treatment of ICH and ICIP as intangible assets within an Australian regulatory environment and define an auditing process and accountability model incorporating cultural, social and environmental measures. A central tenet of this model relates to improving levels of personal and commercial financial literacy in the First Nation participants. Collectively, these factors promote informed participation and decision-making, and may promulgate more sustainable outcomes. Social implications: Integrated thinking requires all these factors to be considered in a holistic manner, such that a First Nation enterprise and the wider Aboriginal and Torres Strait Islander people can understand, and make decisions based on, the overall impact it has on all their stakeholders and generally on the society, the environment and the economy. Originality/value: This paper contributes to Australia's strategic research priorities of maximising social and economic participation in society and improving the health and well-being of the Aboriginal and Torres Strait Islander people. The authors address the inability of current Western accounting standards, practices and models to suitably account for communally held and protocol-bound intangible Indigenous cultural heritage and Indigenous cultural intellectual property assets.